Covid-19 information from the three most widely read newspapers in Europe. Differences and convergences - Nicola Strizzolo; Massimiliano Moschin (Studia i Analizy Nauk o Polityce, 2021)
Our study aims to understand the mutability of virus-related discourses by tracing common points of reference. To do so, we chose three newspapers from as many European states and monitored each mid-month Wednesday during the first wave of Covid-19: January to October 2020. The newspapers investigated were those with the largest audience: Corriere della Sera (Italy), Das Bild (Germany), and The Sun (United Kingdom). To do so, we used categories such as context, frame, and theme. We sifted the corpus, comprising 1175 articles, with Atlas.ti. Based on the categories used and their frequency, we reconstructed contextualization, framing, and thematization – all at a more abstract level. On content revolving around the keywords Covid-19 and Coronavirus, the only differences that emerged were a greater interest in sports for The Sun and vacations for Das Bild. All the newspapers considered granting little space to the weakest areas of the population: disabled or young people, women, immigrants, and the unemployed.